KEARIFAN LOKAL BAHASA DAN BUDAYA MASYARAKAT NELAYAN PANTAI SELATAN KABUPATEN PURWOREJO - Bagiya Bagiya (p-ISSN 2356-0576, 2018)
Abstract: This study is a qualitative descriptive study the local wisdom in the Java language and culture of the fishing communities on the south coast of perspective entholinguistic Purworejo. The purpose is to describe (1) the background of what is affecting local wisdom in the language and culture of coastal fishing communities south of Purworejo, (2) local wisdom behind the language and culture of Java, which is reflected in the expression of verbal and nonverbal and public perception of fishermen of folklore in the south coast of Purworejo, and (3) local wisdom contained in the language and culture of the fishing communities on the south coast of Purworejo. This study is a description of the language and culture of the southern coastal fishing communities Purworejo. The data source of this study include (1) the source data from a resource or informant chosen (2) the source of the particles of the event, the behavior of fishermen and (3) a written source. Furthermore, data collection techniques by active observation of interactive , in-depth interviews and ethnographic data analysis method The results of this study include (1) the background of local wisdom fishing community in the southern coastal district of Purworejo include: related religion, people's views on: the economy, education, agriculture, fisheries and culture, (2) local wisdom behind the language and culture of Java reflected in the expression of verbal and nonverbal and public perception of fishermen of folklore in the southern coastal district of Purworejo, among others larungan, kuda lumping, nyadran, resik desa, wiwitan, metikpari, dadabong and jiduran or jibangan (3) local wisdom include: community choices for selection Islam aboge, understanding fishing communities on the economy, education, agriculture, fisheries and culture .